Multisystem inflammatory syndrome in children and Kawasaki disease - Lupu, Ancuta; Gavrilovici, Cristina; Mihai, Cristina Maria; Tonco, Denisa Claudia; Nedelcu, Alin Horatiu; Pertea, Leonard; Chisnoiu, Tatiana; Baciu, Ginel; Stoicescu, Ramona Mihaela; Salaru, Delia Lidia; Badescu, Minerva Codruta; Cuciureanu, Magdalena; et al. (Frontiers in Immunology, 2025)
This narrative review aims to analyze and compare the current literature on multisystem inflammatory syndrome in children (MIS-C) and Kawasaki disease (KD), with a focus on case definitions, clinical features, diagnostic approaches, treatment strategies, and outcomes. Through a comprehensive review of relevant studies, including screening titles, abstracts, and full-text articles, key similarities and differences were identified. Both MIS-C and KD involve immune system dysregulation and share clinical manifestations such as rash, gastrointestinal symptoms, and cardiovascular involvement, with treatments often centered around immunomodulatory therapies. However, significant differences were observed, particularly in terms of age distribution, demographic prevalence, clinical presentation, and diagnostic criteria, with KD primarily affecting younger children and being associated more prominently with coronary artery abnormalities. While both diseases raise concerns about severe cardiac involvement and the need for intensive care, their pathogenic mechanisms have not been fully understood. Ongoing research is critical to elucidating these mechanisms, refining diagnostic criteria, and optimizing therapeutic approaches to improve outcomes for affected children. This comparative analysis is essential for advancing the understanding of both conditions, as accurately distinguishing between MIS-C and KD has significant implications for clinical decision-making and patient management. Given their overlapping yet distinct clinical features, precise differentiation is critical for ensuring timely diagnosis, optimizing therapeutic strategies, and improving patient outcomes. The concern among pediatric patients stems from the potential for severe complications, particularly cardiac involvement, which underscores the need for heightened awareness, early recognition, and evidence-based treatment strategies to minimize long-term morbidity and mortality.